Neglecting Islamic Law in the Distribution of Inheritance in the Sasak Muslim Society: A Study of Legal Pluralism - Wahyuni, Sri; Siregar, Putri Ananda Saka; Rahmatullah (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
This study examines the persistence of Sasak customary inheritance practices within a predominantly Muslim society, focusing on their implications for gender justice through the lens of legal pluralism. Despite the normative authority of Islamic inheritance law (farā’iḍ), the Sasak community continues to prioritize a patrilineal customary system that allocates inheritance exclusively to male heirs, thereby excluding women. Using an empirical socio-legal approach, this research draws on in-depth interviews, observations, and engagement with community members, customary leaders, and religious authorities. The findings reveal that customary law maintains strong social legitimacy due to deeply internalized traditions, reflecting Max Weber’s concept of traditional social action. In this context, inheritance practices are shaped more by habitual norms than by formal religious or legal rationality. The authority of customary leaders often surpasses that of Islamic religious figures, contributing to the marginalization of Islamic inheritance law. This dynamic results in the systematic exclusion of women from inheritance rights, reinforcing gender inequality and negatively affecting women’s socio-economic welfare. The study contributes to the discourse by highlighting the gap between normative Islamic law and its practical implementation, calls for strengthening legal awareness and institutional engagement to promote more equitable inheritance practices.